EFFECTS OF CORONAVIRUS ON THE FETUS - Dadamuxammedova Xolida (Journal Park Publishing, 2022)
In December 2019, the first case of COVID-19, which manifests itself as severe acute respiratory syndrome caused by a new strain of coronavirus (SARS-CoV-2), was reported in Wuhan province. Since then, its rapid and widespread distribution has become an urgent problem for the entire world community.
Keywords: COVID-19; SARS-CoV-2; coronavirus